2017
DOI: 10.1037/bne0000197
|View full text |Cite
|
Sign up to set email alerts
|

Flavors paired with internal pain or with nausea elicit divergent types of hedonic responses.

Abstract: Pairing a taste with either internal pain (e.g., from hypertonic saline injection) or nausea (e.g., from LiCl administration) will reduce subsequent consumption of that taste. Here we examine the responses to a taste paired with either hypertonic saline or LiCl using the analysis of licking microstructure (mean lick cluster size: Experiments 1-3), taste reactivity (examining the distribution of appetitive and aversive orofacial responses: Experiments 2-3), and immobility (as a measure of fear: Experiments 2-3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 58 publications
(128 reference statements)
3
21
0
Order By: Relevance
“…A one dimensional account of palatability would suggest that treatments which produce equivalent effects on appetitive responses should also have equivalent effects on aversive responseswhich is not the case here. Moreover, in a previous study (Dwyer et al, 2017), we demonstrated that pairing a flavor with either nausea or internal pain to the point that both appetitive responses and consumption were completely suppressed (and lick cluster size greatly reduced), only nausea-paired flavors showed increases in aversive reactions, while the pain-paired flavor elicited greater levels of immobility. In summary, many negative USs share the ability to reduce positive aspects of hedonic reactions, but there are reliable differences between them (in particular between emetic and non-emetic treatments) in the ability to induce either conditioned disgust or conditioned fear that cannot be explained simply in terms of differing levels of aversion (for an extended discussion of this issue, see Dwyer et al, 2017).…”
Section: Discussionmentioning
confidence: 61%
“…A one dimensional account of palatability would suggest that treatments which produce equivalent effects on appetitive responses should also have equivalent effects on aversive responseswhich is not the case here. Moreover, in a previous study (Dwyer et al, 2017), we demonstrated that pairing a flavor with either nausea or internal pain to the point that both appetitive responses and consumption were completely suppressed (and lick cluster size greatly reduced), only nausea-paired flavors showed increases in aversive reactions, while the pain-paired flavor elicited greater levels of immobility. In summary, many negative USs share the ability to reduce positive aspects of hedonic reactions, but there are reliable differences between them (in particular between emetic and non-emetic treatments) in the ability to induce either conditioned disgust or conditioned fear that cannot be explained simply in terms of differing levels of aversion (for an extended discussion of this issue, see Dwyer et al, 2017).…”
Section: Discussionmentioning
confidence: 61%
“…Recent work supports the idea that CTAs induced with LiCl or hypertonic saline involve a decrease in both intake and palatability, but that these dissimilar CTA-inducing USs may result in some differential behavioral responses (Dwyer, Gasalla, Bura, & Lopez, 2017). Dwyer and colleagues compared CTAs induced by either LiCl or hypertonic saline as assessed by taste reactivity and voluntary intake, while monitoring locomotor activity (to determine fear-induced freezing) during the taste reactivity trials.…”
Section: Discussionmentioning
confidence: 71%
“…Also, as in the Pelchat et al (1983) study, certain design choices may not have been optimal, including sequential rather than concurrent lick and taste reactivity analysis as well as context changes between conditioning and test trials, which may influence behavior during extinction. Nonetheless, the results of Dwyer et al (2017) raise the possibility that, while many stimuli can produce CTA, nausea-inducing stimuli may have a particularly profound influence on conditioned gaping. Conversely, painful stimuli may have an equally profound effect on measures of fear-like behavior, such as freezing.…”
Section: Discussionmentioning
confidence: 96%
“…In some cases, intraoral infusions of saccharin elicited other aversive behavioral responses including dripping of the fluid from the mouth [a behavior consistent with responses to concentrated quinine (Grill & Norgren ) and tastants paired with illness (Dwyer et al . )], as well as face wipes, forelimb flails, head shakes and mouth‐to‐floor wiping (Grill & Norgren ; Berridge ; Berridge ). Animals that exhibited a high frequency of these other aversive behaviors were analyzed separately (Supporting Information).…”
Section: Methodsmentioning
confidence: 99%